Debt Relief Under the HIPC Initiative : Context and Outlook for Debt Sustainability and Resource Flow - Ross, Doris (IMF Working Papers; Working Paper ;, 2001)
This paper discusses the Heavily Indebted Poor Countries (HIPC) Initiative in the perspective of sizable historical debt relief and large positive net resource flows to HIPCs. It argues that, by substantially reducing HIPCs' debt stocks and debt service payments, the Initiative provides a solid basis for debt sustainability and room for increased social spending. For poverty reduction, HIPC relief is important but broader international support is needed. The paper maintains that, as experience has shown, external support can be effective only if it reinforces sound policies implemented by HIPCs themselves. Thus, debt relief and official development assistance are critical as 'help for self-help.'.